Mapping Local Cytosolic Enzymatic Activity in Human Esophageal Mucosa with Porous Silicon Nanoneedles. (21st July 2015) - Chiappini, Ciro; Campagnolo, Paola; Almeida, Carina S.; Abbassi‐Ghadi, Nima; Chow, Lesley W.; Hanna, George B.; Stevens, Molly M.
<x xml:space="preserve">Abstract</x> Porous silicon nanoneedles can map Cathepsin B activity across normal and tumor human esophageal mucosa. Assembling a peptide‐based Cathepsin B cleavable sensor over a large array of nanoneedles allows the discrimination of cancer cells from healthy ones in mixed culture. The same sensor applied to tissue can map Cathepsin B activity with high resolution across the tumor margin area of esophageal adenocarcinoma.